The big showdown [large type] : a Caleb York western - Spillane, Mickey, 1918-2006 (Spillane, Mickey, 1918-2006. Caleb York western, 2016)
Caleb York has made up his mind and packed his bags. He'll be on the next stage, bound for San Diego and a new life as a Pinkerton man. But before Caleb can say a proper goodbye to his sweetheart, Willa, a peaceful morning erupts into blazing gunfire. Someone has to bring law and order to the wild little town of Trinidad, even as a band of outlaw brothers rides the vengeance trail and a new cattle baron sets his sights on more land ... and on Willa, too. Looks like Caleb will be staying on for a while.